Determinants of physical activity behavior among older adults with subjective cognitive decline based on the capability, opportunity, motivation, and behavior model: mediating and moderating effects - Chen, Yiping; Li, Wei; Yang, Hui (Frontiers in Public Health, 2024)
Background: PA is vital for secondary prevention in older adults with subjective cognitive decline (SCD), but their physical activity (PA) levels are low, and the underlying interaction pathways among associated factors are poorly understood. This study aims to identify mediating and moderating effects of determinants on PA behavior in older adults with SCD using the capability, opportunity, motivation, and behavior model. Methods: Following the STROBE checklist, we conducted a cross-sectional survey among 289 older adults with SCD. Path regression, mediation effects, and moderation effects were used to explore the associated factors of PA behavior and the associations among these variables. Results: The prevalence of physical inactivity among older adults with SCD was high (40.3%). The path model fit indices were χ²/df = 1.145, GFI = 0.968, CFI = 0.988, and RMSEA = 0.022. Path regression revealed that frailty, physical and social support, PA motivation, and fall history had significant direct association with PA behavior. PA motivation not only partially mediates between frailty and PA behavior but also partially mediates between physical and social support and PA behavior. Additionally, fall history moderated the relationship between frailty and PA behavior. Conclusion: PA behavior in older adults with SCD requires improvement. Healthcare professionals should devise more effective interventions to boost PA behavior by enhancing motivation. Screening for frailty and addressing fall history, while providing sufficient physical and social support, is crucial.